Itu Kebiasaan Makan dengan Kejadian Dispepsia Pada Remaja: Kebiasaan Makan dengan Kejadian Dispepsia Pada Remaja - Rahmat Hidayat; Agung Susanto; Anik Lestari (Amerta Nutrition, 2023)
Background: All over the world the prevalence of dyspepsia is quite high. Various literature sources in western countries show that the prevalence of dyspepsia Various literature sources in western countries show that the prevalence of dyspepsia is in the range of 7-41% in 2009, but unfortunately only about 10-20% of patients seek treatment or medical help. The increasing condition of dyspepsia can cause various health problems such as decreasing quality of life and functional activity. Dyspepsia usually affects those of productive age. Objectives: This article was produced with the intention of examining the association between eating behaviors and the prevalence of dyspepsia in adolescents. Methods: This is a qualitative article written using a literature study through searches on Google, Google Scholar and Research Gate with the keywords “Eating Patterns and Dyspepsia”, “Types and Frequency of Eating and Dyspepsia”, and “Risk Factors for Dyspepsia”. The resulting articles were selected using the PRISMA flowchart. Results: There are still many teenagers who do not take care of their own health. Teenagers who still live with their parents sometimes still don't care about their health. Adolescents' eating habits, such as eating irregularly or experimenting with an unbalanced diet that is not recommended by health professionals, can lead to unfulfilled nutritional needs. Conclusions: Today's lifestyle of teenagers influences their eating habits. Teenagers who are preoccupied with schoolwork and other activities often delay eating or apply the wrong diet, which if left unchecked can trigger dyspepsia. There is a need for repeated education about the importance of fulfilling nutritional intake through regular eating habits to reduce dyspeptic symptoms.